2022
DOI: 10.1088/1361-6595/ac6d0c
|View full text |Cite
|
Sign up to set email alerts
|

Energy exchange modulation for selective control of gas temperature and electron number density in cold atmospheric plasmas

Abstract: Selective control of the key parameters of the cold atmospheric plasmas (CAPs) is crucial for diverse applications ranging from materials processing, clinical medicine to clean energy generation. In particular, the low gas temperature (T g) and high electron number density (n e) are both critical for obtaining high treatment efficiency of heat-sensitive materials, yet are challenging to achieve because of very frequent species collision nature in CAPs. In this letter, select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It analyzed the effects of argon flow and input power on electron density. A recent study utilizing the 'energy tree' concept and numerical modeling has revealed distinctive non-equilibrium energy transfer pathways, offering the potential for selective manipulation of gas temperature and electron density in cold atmospheric plasmas [23]. Using the Thomson scattering and electric field-induced second harmonic methods, Li et al [24] found that the brightness of plasma plumes in different states is mainly controlled by electron temperature rather than electron density.…”
Section: Introductionmentioning
confidence: 99%
“…It analyzed the effects of argon flow and input power on electron density. A recent study utilizing the 'energy tree' concept and numerical modeling has revealed distinctive non-equilibrium energy transfer pathways, offering the potential for selective manipulation of gas temperature and electron density in cold atmospheric plasmas [23]. Using the Thomson scattering and electric field-induced second harmonic methods, Li et al [24] found that the brightness of plasma plumes in different states is mainly controlled by electron temperature rather than electron density.…”
Section: Introductionmentioning
confidence: 99%